Princípio republicano, inclusão e o direito fundamental à educação - Daloia, Lucas Antonio Pires (2022)
The present work aims to carry out an analysis of the normative position of inclusion in the midst of the 1988 Constitution, exposing its legal nature, its structure and deepening the design of the mesh of guarantees that are placed in the outline of the constitutional system of education. Starting from an analysis of the concept, nature and behavior of legal principles, the work proposes brings an approach of the republican principle as established by the text of the Brazilian Constitution, considering the way in which it faces the facticity of the country, in order to seek meaning and content of the rule in question, locating the position of inclusion in the midst of its legal regime. From then onwards, it addresses the role of legal guarantees as essential elements to its outline, from the contrast between rights and duties that mark the constitutional framework. Thus, it seeks to explore inclusion from its position as an axiological element of the order to support guarantee structures. Therefore, the constitutional design of the right to education is observed, in order to understand, from the weight it has for the constitutional design, how these are established